Drug-Induced Hypersensitivity Syndrome: A Clinical, Radiologic, and Histologic Mimic of Lymphoma - Faaria Gowani; Bradley Gehrs; Teresa Scordino (Case Reports in Hematology)
Drug-induced hypersensitivity syndrome (DIHS; also known as drug reaction with eosinophilia and systemic symptoms, or DRESS) is a rare, potentially life-threatening condition that typically presents 2–8 weeks after drug exposure with fever, rash, organ dysfunction, and lymphadenopathy. Here, we describe the case of an 18-year-old African American female who presented with cervical lymphadenopathy, fevers, and a macular rash. A PET scan showed diffuse hypermetabolic lymphadenopathy suggestive of lymphoma, with involvement of the spleen and kidneys. The clinical history, imaging, and biopsy findings initially raised concern for a malignant process, with a differential diagnosis including classic Hodgkin’s lymphoma and T-cell lymphoma. However, the morphologic and immunophenotypic features were not entirely typical for those diagnoses. The patient was ultimately diagnosed with DIHS after it was learned that she recently had been treated with minocycline, a medication previously implicated in causing DIHS.